Adolescents' Self-Determined Motivation to Learn About Safer Sex Online - Thomas Gültzow; Ellis Driehuizen; Hanne Zimmermann; Eline Smit (University of Zurich, IKMZ - Department of Communication and Media Research, 2023)
Self-determined motivation fosters better learning and sustained health behaviour adoption than controlled motivation. Self-determined motivation can be strengthened by satisfying the need for autonomy. Therefore, this study investigated if adolescents' (1) intrinsic motivation to learn about safer sex and (2) self-determined motivation to perform safer sex would be higher when an online message is presented in autonomy-supportive language compared to controlling language. Furthermore, this study also investigated if adolescents' (1) intrinsic motivation to learn about safer sex and (2) self-determined motivation to perform safer sex changes depending on whether the online message is written by someone that is similar to them. To this end, a 2 (autonomy-supportive language vs. controlling language) x 2 (identification vs. no identification) experimental study (N = 214) was conducted using a website page about safe sex from the Dutch sexual health website sense.info. Even though we found some indications of the expected effects, a two-way analysis of covariance (ANCOVA) showed no significant difference for either autonomy-supportive language, identification, or an interaction of both strategies. However, we found some preliminary evidence that this could be due to a ceiling effect. We therefore recommend further exploring these strategies, considering some lessons learned.